VSG Frequency Regulation Strategy for Adaptive Model Predictive Control - Sun, Shida; Liu, Tongliang; Deng, Yinxi (International Journal of Mechanical and Electrical Engineering, 2024)
When the active power of a Virtual Synchronous Generator (VSG) is unbalanced, the frequency will fluctuate significantly. Based on this, this article proposes an adaptive model predictive control method. By introducing a hyperbolic tangent function to construct an adaptive moment of inertia that includes frequency change and frequency change rate to provide the inertia for the island microgrid system, and the predicted model is updated in real-time; At the same time, model predictive control is used to calculate the optimal power reference value of VSG, strengthening the power support of VSG. The results indicate that under joint control improves the frequency regulation capability of VSG units and further enhances the system frequency performance, and the frequency deviation reduces from 0.15Hz to 0.05Hz, and the frequency change rate reduces from 0.58Hz/s to 0.5Hz/s. It is proved that the proposed control strategy can effectively suppress the maximum frequency offset and maximum frequency change rate during power fluctuations.